Selected health problems and socio-demographic characteristics of female headed families in the medical officer of health area Kanthale - Costa, D.G.M (My University, 2003)
FHF were equally distributed among the ethnic and religious groups in Kanthale. Their levels of education,economy,and opportunity for employment was poor. More than the half of them were psychologically distressed. There was a significant association between psychological distress and physical illness (hypertension and migraine).They had practiced emotional focused coping strategies than the problem focused coping strategies